Electron localisation function in current-density-functional theory - Furness, James W.; Ekström, Ulf; Helgaker, Trygve; Teale, Andrew M. (Taylor & Francis, 2016)
We present a generalisation of the electron localisation function (ELF) to current-density-functional theory as a descriptor for the properties of molecules in the presence of magnetic fields. The resulting current ELF (cELF) is examined for a range of small molecular systems in field strengths up to B0 = 235 kT (one atomic unit). The cELF clearly depicts the compression of the molecular electronic structure in the directions perpendicular to the applied field and exhibits a structure similar to that of the physical current densities. A topological analysis is performed to examine the changes in chemical bonding upon application of a magnetic field.